Internal Assessment of Students in Mathematics at the Basic Level: Teachers' Perspectives - Gnawali, Yagya Prasad; Sharma, Bishnu (Nepalese Journal of Development and Rural Studies, 2024)
This study explores the internal assessment system in basic school-level mathematics from the perspectives of teachers, with the primary aim of evaluating how internal assessments are conducted and their alignment with actual classroom practices. Utilizing a quantitative research methodology within a survey design, data were collected from 80 mathematics teachers across 40 schools. Grounded in the post-positivist paradigm, the study adhered to the assumptions of a single social reality, objectivity, and a value-free axiology. For data analysis, Cronbach’s alpha was employed to assess the reliability of the research instruments, Exploratory Factor Analysis (EFA) was used to identify underlying dimensions, one-sample t-tests were applied to determine agreement or disagreement with key statements, and Cohen’s d was used to interpret effect sizes. The findings revealed that internal assessment practices are largely focused on assigning numerical grades to enhancement student results rather than fostering for learning. Teachers reported difficulties in maintaining systematic records of internal assessments. Despite the clarity of the policy, its guidelines were not consistently followed in actual classroom settings. The study emphasized the urgent need for capacity-building training programs aimed at enhancing teachers’ understanding and competencies in implementing internal assessments as meaningful tools for improving student learning, rather than as mere administrative formalities.